COVID-19 Therapeutics and Vaccines: A Race to Save Lives. (4th November 2021) - Bebenek, Ilona; Bannister, Roy; Dubinion, John; Fortin, Marie; Liu, Matt; Motter, Arianne L; Rohde, Cynthia M; Wrzesinski, Claudia
Abstract: COVID-19 (Coronavirus Disease 2019), the disease caused by SARS-CoV-2 (Severe Acute Respiratory Syndrome Coronavirus-2) is an ongoing global public health emergency. As understanding of the health effects of COVID-19 has improved, companies and agencies worldwide have worked together to identify therapeutic approaches, fast-track clinical trials and pathways for emergency use, and approve therapies for patients. This work has resulted in therapies that not only improve survival, reduce time of hospitalization, and time to recovery, but also include preventative measures, such as vaccines. This manuscript discusses development programs for 3 products that are approved or authorized for emergency use at the time of writing: VEKLURY (remdesivir, direct-acting antiviral from Gilead Sciences, Inc.), REGEN-COV (casirivimab and imdevimab antibody cocktail from Regeneron Pharmaceuticals Inc.), and Comirnaty (Pfizer-BioNTech COVID-19 Vaccine [Pfizer, Inc.-BioNTech]), and perspectives from the U.S. Food and Drug Administration.